Thermomechanical and Photophysical Properties of Crystal-Violet-Dye/H2O Based Dissolutions via the Pulsed Laser Photoacoustic Technique - Vicente Torres-Zúñiga; Rosalba Castañeda-Guzmán; Santiago J. Pérez-Ruiz; Omar G. Morales-Saavedra (Advances in Materials Science and Engineering)
Different thermoelastic parameters, for example, the acoustic attenuation and the speed of sound, are fundamental for instrumental calibration and quantitative characterization of organic-based dissolutions. In this work, these parameters as functions of the concentration of an organic dye (crystal-violet: CV) in distillated water (H2O) based dissolutions are investigated. The speed of sound was measured by the pulsed-laser photoacoustic technique (PLPA), which consists in the generation of acoustic-waves by the optical absorption of pulsed light in a given material (in this case a liquid sample). The thermally generated sound-waves traveling through a fluid are detected with two piezoelectric sensors separated by a known distance. An appropriate processing of the photoacoustic signals allows an adequate data analysis of the generated waves within the system, providing an accurate determination of the speed of sound as function of the dye-concentration. The acoustic attenuation was calculated based on the distance of the two PZT-microphones to an acoustic-source point and performing linear-fitting of the experimental data (RMS-amplitudes) as function of the dye-concentration. An important advantage of the PLPA-method is that it can be implemented with poor or null optical transmitting materials permitting the characterization of the mechanical and concentration/aggregate properties of dissolved organic compounds.